Impact of interorganelle coordination between the conventional early secretory pathway and autophagy in cellular homeostasis and stress response - Tapia, Diego; Cavieres, Viviana A.; Burgos, Patricia V.; Cancino, Jorge (Frontiers in Cell and Developmental Biology, 2023)
The conventional early secretory pathway and autophagy are two essential interconnected cellular processes that are crucial for maintaining cellular homeostasis. The conventional secretory pathway is an anabolic cellular process synthesizing and delivering proteins to distinct locations, including different organelles, the plasma membrane, and the extracellular media. On the other hand, autophagy is a catabolic cellular process that engulfs damaged organelles and aberrant cytosolic constituents into the double autophagosome membrane. After fusion with the lysosome and autolysosome formation, this process triggers digestion and recycling. A growing list of evidence indicates that these anabolic and catabolic processes are mutually regulated. While knowledge about the molecular actors involved in the coordination and functional cooperation between these two processes has increased over time, the mechanisms are still poorly understood. This review article summarized and discussed the most relevant evidence about the key molecular players implicated in the interorganelle crosstalk between the early secretory pathway and autophagy under normal and stressful conditions.